Novel room-temperature perylene liquid crystals: synthesis of 1, 7-dibrominated cholesterol–perylene bisimides with different ester-bridging chains and their mesomorphic properties. Issue 12 (25th September 2016) - Zhu, Mingguang; Guo, Hongyu; Yang, Fafu; Wang, Zusheng
ABSTRACT: Three novel 1, 7-dibrominated cholesterol–perylene liquid crystals6a, 6b and6c with different ester-bridging chains were designed and synthesised in yields of 30–40%. Their structures were characterised by FT-IR, 1 H NMR and HR-MS spectra. Their mesomorphic behaviours were studied by differential scanning calorimetry (DSC), polarising optical microscopy (POM) and X-ray diffraction (XRD). Compounds6a, 6b and6c exhibit hexagonal columnar liquid crystalline phase at room temperature. Their mesomorphic temperature ranges are as wide as 140–162°C. Their fluorescence spectra suggested that they possess good fluorescence properties in solution. The soft ester-bridging chains are more favourable for room-temperature mesophase and high fluorescence than the rigid ester-bridging chain. GRAPHICAL ABSTRACT: